Rectilinear Motion Anomaly (Garavity Anomaly) Around Mount Kelud - Kamilia Nisa'i; Ainun Rahmatun Nisak; Oscar Afif; Indah Tian Permatasari (Yayasan Adra Karima Hubbi, 2024)
Indonesia is a country that is prone to geological disasters due to volcanic eruptions, ground movements, earthquakes and tsunamis, due to its location at the meeting point of three active tectonic plates: the Eurasian, Pacific and Indo-Australian plates. Geophysical research is important in understanding this phenomenon by utilizing physical parameters to study the earth beneath the surface. Gravity methods show potential in providing detailed images of geological structures and rock density contrasts, especially in geothermal investigations. Mount Kelud, as one of the active volcanoes in Indonesia, is the focus of this research. By using a geophysical method approach, this research aims to analyze the gravity anomalies around Mount Kelud. It is hoped that this study will provide a deeper understanding of the gravitational anomaly phenomenon in the region, which can be useful in future disaster mitigation and management efforts.